Odpowiedzi

2013-07-19T13:52:57+02:00

x     1     2      3      4      6     12

------------------------------------------

y      2    9     20    35    77   299

 

f(1)=2+1-1=2

f(2)=2*4+2-1=9'

f(3)=2*9+3-1=20

f(4)=2*16+4-1=35

f(6)=2*36+6-1=77

f(12)=2*144+12-1=299

2013-07-19T14:25:32+02:00

y = 2x² + x - 1

D = {1,2,3,4,6,12}

 

f(1) = 2*1² + 1 - 1 = 2

f(2) = 2*2² + 2 - 1 = 9

f(3) = 2*3² + 3 - 1 = 20

f(4) = 2*4² + 4 - 1 = 35

f(6) = 2*6² + 6 - 1 = 77

f(12) = 2*12² + 12 - 1 = 299

 

x      1       2        3        4        6        12

-----------------------------------------------------

y      2       9       20       35     77       299